Análise estrutural em turbiditos ediacaranos da Pedreira Belagres, Bacia do Camaquã – RS - (:unkn) unknown (Universidade Federal do Pampa, 2018)
This work describes a geometric and kinematic investigation of tectonic structures in Ediacaran strata of the Belagres Quarry, located southeast of Caçapava do Sul-RS, as well as its implications with the regional structural geological framework. The study revealed the existence of 3 kinematic stages and a geometric arrangement of certain geogragraphically associated structural trends. Elements of the pattern thus formed include folds, faults, veins and joints tendencies. Its causes were interpreted as resulting from the movement of regional shear zones of the region to which the study area is inserted. The first kinematic stage (I) is represented by the normal faults, defined by high-angle to intermediate movements with direction of motion for NW, arranged parallel to the axial trend of the folds. The second Kinematic stage (II) is represented by the inverse faults and defined by high-angle movements with sense of motion for SE, arranged in the same way, parallel to the axial trend of the folds. This compressive regime was interpreted as responsible for folds in the region studied. The third Kinematic stage (III) is represented by the striations on the bedding surface characterized by horizontal to sub-horizontal movements with NNE plunge and interpreted as resulting from the lateral movements of regional transcurrent faults of the same direction, resulting in wide open folds. These structures form a coherent structural framework with a strong genetic relation with the regional brittle tectonics of Ediacarana.
Keywords: Análise geométrica; Análise cinemática; Grupo Bom Jardim; Geometric analysis; Kinematic analysis; Group Bom Jardim; CNPQ::CIENCIAS EXATAS E DA TERRA